2000
DOI: 10.1111/j.1528-1157.2000.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ganaxolone on Flurothyl Seizures in Developing Rats

Abstract: Summary:Purpose: To determine the effects of a newly synthesized epalon, ganaxolone (GNX), on primarily generalized seizures in rats of various ages during development. Epalons are classified as neuroactive steroids that interact at unique site of the GABA, receptor-CI-channel complex in the central nervous system.Methods: Sprague-Dawley male rats were used at 9, 15, 30, and 60 postnatal days (PN). GNX dissolved in 2-hydroxypropyl-P-cyclodextrine was administered intraperitoneally in different doses at various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…More recently, pretreatment with ganaxolone, a neuroactive steroid, delayed and reduced NMDA spasms in the prenatal betamethasone model (Yum et al 2014). The therapeutic relevance of ganaxolone in IS is currently unclear because the effect on spasms or flurothyl seizures was only observed with high doses that can produce motor impairment (Liptakova et al 2000; Yum et al 2014). In a multicenter open label, add-on clinical trial of ganaxolone in infants with refractory IS, 33% of the infants responded with at least 50% reduction in spasms but only one of the 15 patients became spasm-free (Kerrigan et al 2000).…”
Section: West Syndrome and Infantile Spasmsmentioning
confidence: 99%
“…More recently, pretreatment with ganaxolone, a neuroactive steroid, delayed and reduced NMDA spasms in the prenatal betamethasone model (Yum et al 2014). The therapeutic relevance of ganaxolone in IS is currently unclear because the effect on spasms or flurothyl seizures was only observed with high doses that can produce motor impairment (Liptakova et al 2000; Yum et al 2014). In a multicenter open label, add-on clinical trial of ganaxolone in infants with refractory IS, 33% of the infants responded with at least 50% reduction in spasms but only one of the 15 patients became spasm-free (Kerrigan et al 2000).…”
Section: West Syndrome and Infantile Spasmsmentioning
confidence: 99%
“…Ganaxolone has similar pharmacological properties to the natural neurosteroids such as allopregnanolone (Reddy and Woodward, 2004). It has protective activity in diverse rodent seizure models, including clonic seizures induced by the chemoconvulsants pentylenetetrazol, bicuculline, flurothyl, aminophylline; limbic seizures in the 6-Hz model; amygdala and cocaine-kindled seizures; and corneal kindled seizures (Gasior et al, 2000; Liptáková et al, 2000; Reddy and Rogawski, 2000a, 2010b; Kaminski et al, 2003, 2004). During prolonged daily treatment, tolerance does not develop with the anticonvulsant activity of ganaxolone (Kokate et al, 1998; Reddy and Rogawski, 2000a).…”
Section: Neurosteroid Therapy Of Epilepsymentioning
confidence: 99%
“…Electrophysiological recordings showed that nanomolar concentrations of GNX potentiated GABA-evoked chloride currents in Xenopus oocytes expressing human GABA-A receptor subunits α1, β2, γ2L, but direct activation of chloride flux occurred only at micromolar concentrations 14,15 .…”
Section: Discussionmentioning
confidence: 99%